HOW TO TEACH SPEAKING TO ESP STUDENTS USING TECHNOLOGY (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article provides tips and advice on teaching ESP (English for Specific Purposes) students to speak using technology. This article outlines online resources, speaking exercises, speech recognition programs, online discussion forums, virtual language labs, and other technology-based ways for ESP students to learn to speak. These techniques make it easier for students to learn to speak and help them improve their speaking skills. The article also notes that in order to change the old teaching methods, teachers should also learn convenient, reliable and effective teaching methods for ESP students to learn to speak. The article provides good information on methods and resources for ESP students to use technology to help them learn to speak. This information will be useful for teachers and students and will help students improve their speaking and listening skills. This article shows ESP students easy, reliable and effective methods for learning to speak, and these methods can be well used in the future teaching process for teachers and students.